2005
DOI: 10.1113/jphysiol.2005.084186
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species contribute to the presynaptic action of extracellular ATP at the frog neuromuscular junction

Abstract: During normal cell metabolism the production of intracellular ATP is associated with the generation of reactive oxygen species (ROS), which appear to be important signalling molecules. Both ATP and ROS can be released extracellularly by skeletal muscle during intense activity. Using voltage clamp recording combined with imaging and biochemical assay of ROS, we tested the hypothesis that at the neuromuscular junction extracellular ATP generates ROS to inhibit transmitter release from motor nerve endings. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 53 publications
(114 reference statements)
1
43
1
Order By: Relevance
“…Sigmoid movement depends on acetylcholine (ACh) neurotransmission as well but in our experiments appears unaffected by heat shock treatment. These results concurred with reports that ROS actions do not deactivate nicotinic acetylcholine receptors (nAChR) at the neuromuscular junction (Ben-Haim et al 1973;Giniatullin et al 2005) On the contrary, ROS and heat shock inhibit or deactivate enzyme acetylcholinesterase (Eichler and Silman 1995), keeping the ACh action longer in the synaptic cleft.…”
Section: Discussionsupporting
confidence: 81%
“…Sigmoid movement depends on acetylcholine (ACh) neurotransmission as well but in our experiments appears unaffected by heat shock treatment. These results concurred with reports that ROS actions do not deactivate nicotinic acetylcholine receptors (nAChR) at the neuromuscular junction (Ben-Haim et al 1973;Giniatullin et al 2005) On the contrary, ROS and heat shock inhibit or deactivate enzyme acetylcholinesterase (Eichler and Silman 1995), keeping the ACh action longer in the synaptic cleft.…”
Section: Discussionsupporting
confidence: 81%
“…To test whether the potentiating effect of ATP on GABAergic SPSCs was mediated by ROS, we used the antioxidant NAC, which is a widely used ROS scavenger (5,27). The action of ATP on SPSCs was prevented by NAC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ROS Imaging-The above mentioned experiments clearly indicated that ATP is able to induce calcium transient in astrocytes via P2Y 1 receptors. To directly test whether ATP triggers ROS generation in astrocytes, we performed imaging of ROS in brain slices using the fluorescent dye DCF (5,10,21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, much of the evidence for purinergic involvement in skeletal neuromuscular transmission has come from studies of the fish electric organ, frog and chick neuromuscular junctions (see [13] and [14][15][16][17][18][19][20][21]). …”
Section: Skeletal Neuromuscular Junctionmentioning
confidence: 99%